A question of time: How demographic faultlines and deep-level diversity impact the development of psychological safety in teams - Gerlach, Rebecca; Gockel, Christine (Frontiers in Psychology, 2022)
Psychological safety (PS) is a shared belief among team members that it is safe to take interpersonal risks. It can enhance team learning, experimentation with new ideas, and team performance. Considerable research has examined the positive effects of PS in diverse organizational contexts and is now shifting its focus toward exploring the nature of PS itself. This study aims to enhance our understanding of PS antecedents and development over time. Based on the model of team faultlines and research on team diversity, we examined the effects of demographic faultlines, team member personality, and member competencies on the development of PS. Over five months, 61 self-managed teams (N = 236) assessed their PS at the beginning, midpoint, and end of a research project. Results of a multilevel growth curve model show that PS decreased from project beginning to end. Initial levels of PS were especially low when teams had strong demographic faultlines and when team members differed in neuroticism. PS decreased more strongly over time when team members were diverse in agreeableness and assessed their task-related competencies to be relatively high. Our study identifies time and team composition attributes as meaningful predictors for the development of PS. We present ideas for future research and offer suggestions for how and when to intervene to help teams strengthen PS throughout their collaboration.